Effect of Upstream Wake on Shower-Head Film Cooling - Ping-Hei Chen; Jr-Ming Miao (International Journal of Rotating Machinery)
The present study aims to investigate the effect of an upstream wake on the convective transport phenomena over a turbine blade with shower-head film cooling. A naphthalene sublimation technique was implemented to obtain the detailed mass transfer distributions on both suction and pressure surfaces of the test blade. All mass transfer runs were conducted on a blowing-type wind tunnel with a six-blade linear cascade. The leading edge of the test blade was drilled with three rows of equally spaced injection holes. The upstream wake was simulated by a circular bar with the same diameter as that of the trailing edge of the test blade.